2015
DOI: 10.1016/j.molcel.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Condensin I and II Complexes License Full Estrogen Receptor α-Dependent Enhancer Activation

Abstract: Summary Enhancers instruct spatio-temporally specific gene expression in a manner tightly linked to higher-order chromatin architecture. Critical chromatin architectural regulators condensin I and condensin II play non-redundant roles controlling mitotic chromosomes. But aspects of interphase condensin loading and function, or in transcription regulation remain unclear. Here we report that both condensin complexes exhibit an unexpected, dramatic estrogen-induced recruitment to estrogen receptor α (ER-α)-bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 59 publications
3
95
1
Order By: Relevance
“…The identification of ChIP-seq peaks (bound & enriched regions) was performed by using HOMER as previously described ((Li et al, 2015; Liu et al, 2013; Ma and Telese, 2015; Telese et al, 2015). For all the ChIP-seq reads we kept only one tag for each unique genomic position to minimize artifacts due to clonal amplification.…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of ChIP-seq peaks (bound & enriched regions) was performed by using HOMER as previously described ((Li et al, 2015; Liu et al, 2013; Ma and Telese, 2015; Telese et al, 2015). For all the ChIP-seq reads we kept only one tag for each unique genomic position to minimize artifacts due to clonal amplification.…”
Section: Star Methodsmentioning
confidence: 99%
“…Following ligand-induced nuclear entry, ERα binds to ~30,000 estrogen response elements (EREs), a subset of which harbor the histone/epigenetic marks associated to enhancers (Carroll et al, 2006; Li et al, 2013; Hah et al, 2013). At putative functional enhancers, ERα promotes the recruitment of co-factors on these enhancers to activate the transcription of enhancer RNA (eRNA) and target coding genes (Li et al, 2015; Liu et al, 2014; Nagarajan et al, 2014). In addition to the coactivator complexes, it appears that additional factors can be critically required.…”
Section: Introductionmentioning
confidence: 99%
“…As in fission yeast cells, condensin is enriched at highly transcribed genes in higher eukaryotes (Kim et al 2013; Sutani et al 2015). It has recently been shown that condensin mediates gene looping and activation in human cells, and that condensin mutations are significantly accumulated in various cancer types (Li et al 2015; Leiserson et al 2015). Further work in the fission yeast model, addressing how the condensin-TBP interaction contributes to higher-order genome organization, gene regulation, and chromosome segregation, will help elucidate the evolutionarily conserved mechanisms of how condensin organizes eukaryotic genomes and serves as a functional ligature among important cellular processes.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Moreover, these regulatory regions are located hundreds of kilobases away from transcription start sites (TSS) of the target gene (2). Cohesin and condensin have recently been shown to positively regulate transcription by modulating enhancer function and enhancer–promoter looping (3,4). Yet, the role of other architectural proteins involved in nuclear organization, such as the transcriptional regulator CCCTC-binding factor (CTCF), is unexplored.…”
Section: Introductionmentioning
confidence: 99%